ADGRV1 Variants in Febrile Seizures/Epilepsy With Antecedent Febrile Seizures and Their Associations With Audio-Visual Abnormalities - Zhou, Peng; Meng, Heng; Liang, Xiaoyu; Lei, Xiaoyun; Zhang, Jingwen; Bian, Wenjun; He, Na; Lin, Zhijian; Song, Xingwang; Zhu, Weiwen; Hu, Bin; Li, Bingmei; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective ADGRV1 gene encodes adhesion G protein-coupled receptor-V1 that is involved in synaptic function. ADGRV1 mutations are associated with audio-visual disorders. Although previous experimental studies suggested that ADGRV1 variants were associated with epilepsy, clinical evidence is limited and the role of ADGRV1 variants in epilepsy remains elusive. Methods Trio-based targeting sequencing was performed in a cohort of 101 cases with FS and epilepsy with antecedent FS. Protein modeling was used to assess the damaging effects of variants. The genotype-phenotype correlations of the ADGRV1 variants in epilepsy and audio-visual disorders were analyzed. Results ADGRV1 variants were identified in 9 unrelated cases (8.91%), including 2 heterozygous frameshift variants, 6 heterozygous missense variants, and a pair of compound heterozygous variants. These variants presented statistically higher frequency in this cohort than that in control populations. Most missense variants were located at CalX-β motifs and changed the hydrogen bonds. These variants were inherited from the asymptomatic parents, indicating an incomplete penetrance. We also identified SCN1A variants in 25 unrelated cases (24.75%) and SCN9A variants in 3 unrelated cases (2.97%) in this cohort. Contrary to SCN1A variants associated epilepsy that revealed seizure aggravated by sodium channel blockers, ADGRV1 variants were associated with mild epilepsy with favorable responses to antiepileptic drugs. The patients denied problems of audio-visual-vestibular abilities in daily life. However, audio-visual tests revealed auditory and visual impairment in the patient with compound heterozygous variants, auditory or vestibular impairment in the patients with heterozygous frameshift or hydrogen-bond changed missense variants, but no abnormalities in the patients with missense variants without hydrogen-bond changes. Previously reported ADGRV1 variants that were associated with audio-visual disorders were mostly biallelic/destructive variants, which was significantly more frequent in the severe phenotype of audio-visual disorders (Usher syndrome 2) than in other mild phenotypes. In contrast, the variants identified in epilepsy were monoallelic, missense mainly located at CalX-β or affected isoforms VLGR1b/1c. Significance ADGRV1 is potentially associated with FS related epilepsy as a susceptibility gene. The genotype, sub-molecular implication, isoforms, and damaging severity of the variants explained the phenotypical variations. ADGRV1 variants associated FS/epilepsy presented favorable responses to antiepileptic drugs, implying a clinical significance.